Comparison of selected inflammation-based prognostic markers in relapsed or refractory metastatic colorectal cancer patients - Song, Anna (World J Gastroenterol, 2015)
AIM: To investigate the impact of systemic inflammation-based prognostic markers on overall survival in relapsed/refractory metastatic colorectal cancer (mCRC) patients. METHODS: To investigate prognostic markers in mCRC patients, this study was performed with patients who have experienced relapsed/refractory mCRC with standard chemotherapy or were inapplicable to conventional treatment modality because of poor performance status, age, or comorbidity. We reviewed the medical records of 177 mCRC patients managed with Korean Medicine (KM) treatment modality using an anticancer agent of Rhus verniciflua Stokes extract from June 2006 to April 2013. The clinicopathologic characteristics, laboratory test, the systemic inflammation markers including the modified Glasgow prognostic score (mGPS), neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), lymphocyte monocyte ratio (LMR), and prognostic nutritional index (PNI) were analyzed. The overall survival of patients was calculated with the Kaplan-Meier method and the statistical significance was compared using with the log-rank test. To compare the impact of systemic inflammation based markers, the hazard ratio (HR) of mGPS, NLR, PLR, LMR, and PNI for overall survival were evaluated with the Cox proportional hazards regression. RESULTS: The majority of mCRC patients had relapsed/refractory to standard chemotherapy; 128 patients (72.3%) had undergone more than second line chemotherapy, and the median time from diagnosis of mCRC to initiation of KM was 9.4 mo. The median overall survival of enrolled patients was 8.3 mo. On univariate analyses, the inflammation markers of higher mGPS (P < 0.001), NLR ≥ 5 (P < 0.001), PLR > 300 (P = 0.004), LMR ≤ 3.4 (P < 0.001), and PNI ≤ 45.3 (P = 0.001) were significantly associated with decreased survival time. On stepwise multivariate proportional hazards model, mGPS at 2 vs 0 (HR = 3.212, 95%CI: 1.437-7.716, P = 0.004), and LMR ≤ 3.4 (HR = 1.658, 95%CI: 1.092-2.518, P = 0.018) as independent predictors associated with poor overall survival along with carbohydrate antigen 19-9 (HR = 1.482, 95%CI: 1.007-2.182, P = 0.046), AST ≥ 40 (HR = 2.377, 95%CI: 1.359-4.155, P = 0.002), and the treatment duration for KM less than 2.9 mo (HR = 1.718, 95%CI: 1.160-2.543, P = 0.007). CONCLUSION: These results indicate that the inflammatory markers, mGPS and LMR are independent prognostic factors for predicting overall survival in relapsed/refractory mCRC patients.